(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
The development of Physical Anthropology in Nicaragua is approximately 30 years old, its origins are in the investigations of the Department of Anthropology of the National Museum of Nicaragua, when Mrs. Leonor Martínez de Rocha, then director of the Museum, hired a professional in Biology to to take charge of the analysis of ethnozoological and ethnobotanical remains found in archaeological deposits. Doña Leonor had worked from a young age with Don Diocleciano Chavez, Founder of the National Museum Collection and he had made a journalistic report on January 23, 1920 where the information of the finding of mummified human remains found in Punta La Cimarrona, Chiltepe Peninsula - Managua This is one of the first findings linked to Paleoanthropology in Nicaragua. From the 90s it was possible to apply the techniques of Physical Anthropology for the study and characterization